Measuring Service Quality and Developing a Roadmap for the E-Science Service Application at the National Research and Innovation Agency (BRIN) - Pratiwi, Sinta; Taufik, Tatang Akhmad (Institut Teknologi dan Bisnis Bina Sarana Global, 2024)
This research investigates the E-Service Science Application (ELSA) of the National Research and Innovation Agency (BRIN). In 2022, 77.41% of service requests through ELSA were unfulfilled, significantly impacting BRIN's Non-Tax State Revenue (PNBP) and ELSA Points. The study aims to evaluate ELSA's service quality using the Servqual method and to understand user behavior and intentions through the Technology Acceptance Model (TAM) 2. Questionnaires based on Servqual and TAM 2 models were utilized, with data analyzed via descriptive analysis of each variable and Structural Equation Modeling (SEM) using SmartPLS-3 software. Findings revealed that service quality attributes – tangibility, reliability, responsiveness, assurance, and empathy – were unsatisfactory, as indicated by negative GAPs. Importance-Performance Analysis (IPA) was employed to prioritize areas for improvement. Most respondents showed high intention to use (Mean 4.18) and usage behavior (Mean 4.09), with similar ratings for other TAM 2 variables. These insights contribute to the development of an ELSA Application Roadmap, guiding service enhancements and positioning BRIN as a hub for scientific collaboration.